Efforts to Increase Breast Milk Production through Techniques Hypnobreastfeeding in Postpartum Mothers in Tamanan Village, Kediri City in 2023 - Meirna Eka Fitriasnani; Dhita Kris Prasetyanti; Rahma Kusuma Dewi; Fithri Rif’atul Himmah; Siti Khotimah; Yeni Puspita Anggraini (Universitas STRADA Indonesia, 2023)
Hypnobreastfeeding is a relaxation technique that helps smooth the breastfeeding process in a holistic manner that pays attention to the mind, body and soul of breastfeeding mothers. The purpose of this research is to increase breast milk production in postpartum mothers through the hypnobreastfeeding technique. This research design is a pre-experimental one group pretest-posttest design and the population in this study was postpartum mothers. The results showed that half (50%) of the respondents who received good husband support experienced mild anxiety, namely as many as 6 respondents, almost all (76.92%) who received sufficient husband support experienced moderate anxiety, namely as many as 20 respondents. Based on the results of statistical tests using the Wilcoxon signed rank test, it is known that the p value of 0.001 is smaller than the value of α = 0.05 (0.002 < 0.05) so that H0 is rejected and H1 is accepted, meaning that there is an effect of providing hypnobreastfeeding techniques on breast milk production in mothers postpartum in Tamanan Village, Kediri City. Suggestions for research sites to motivate postpartum mothers to try to increase breast milk production by using the hypnobreastfeeding technique.